Repeated dietary exposure to low levels of domoic acid and problems with everyday memory: Research to public health outreach - Grattan, L.; Boushey, Carol; Liang, Y.; Lefebvre, K.; Castellon, L.; Roberts, K.; Toben, A.; Morris, J. (2018)
Domoic Acid (DA) is a marine-based neurotoxin. Dietary exposure to high levels of DA via shellfish consumption has been associated with Amnesic Shellfish Poisoning, with milder memory decrements found in Native Americans (NAs) with repetitive, lower level exposures. Despite its importance for protective action, the clinical relevance of these milder memory problems remains unknown. The purpose of this study was to determine whether repeated, lower-level exposures to DA impact everyday memory (EM), i.e., the frequency of memory failures in everyday life. A cross-sectional sample of 60 NA men and women from the Pacific NW was studied with measures of dietary exposure to DA via razor clam (RC) consumption and EM. Findings indicated an association between problems with EM and elevated consumption of RCs with low levels of DA throughout the previous week and past year after controlling for age, sex, and education. NAs who eat a lot of RCs with presumably safe levels of DA are at risk for clinically significant memory problems. Public health outreach to minimize repetitive exposures are now in place and were facilitated by the use of community-based participatory research methods, with active involvement of state regulatory agencies, tribe leaders, and local physicians.